THE APPLICATION OF TRANSFORMATIONS OF THE GRAVITY AND MAGNETIC FIELD USING AVERAGING METHOD FOR DETERMINATION AND INTERPRETATION OF LOW-AMPLITUDE ANOMALIES - HRYSHCHUK, P.; BULAKH, Ye.; NURMUKHAMEDOV, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
Formulas and graphs of basic component of the potential field for 2-D model with the vertical section – rectangular cell are resulted. The theory of transformation and interpretation of the fields is resulted by the method of comparison due to averaging. The examples of interpretation of the real anomalies and its comparison with drilling data are presented.